Comorbidities in Childhood Celiac Disease: A Phenome Wide Association Study Using the Electronic Health Record. Issue 4 (October 2018) - Prinzbach, Ariana; Moosavinasab, Soheil; Rust, Steve; Boyle, Brendan; Barnard, John A.; Huang, Yungui; Lin, Simon
ABSTRACT: Objectives: Celiac disease (CD) is associated with a variety of extraintestinal autoimmune and inflammatory findings that manifest clinically as symptoms and comorbidities. Understanding these comorbidities may improve identification of the disease and prevent sequelae. In this study, we use an unbiased electronic health record (EHR)-based Phenome Wide Association Study (PheWAS) method to confirm known comorbidities, discover novel associations and enhance characterization of the clinical presentation of CD in children. Methods: Data were extracted from the Nationwide Children's Hospital EHR. Confirmed CD cases (n = 433) were matched with 4330 randomly selected controls. Utilizing an EHR-based PheWAS method to analyze associations of phenotypes with CD, we conducted an unbiased screening of all International Classification of Diseases, 10th revision diagnostic codes and examined significance by performing Fisher's Exact tests. We further tested for the association between CD and 14 previously identified comorbidities in an a priori fashion. Results: We found 45 International Classification of Diseases, 10th revision codes significantly associated with CD. Thirteen are known comorbidities and nine are expected symptoms of CD, thus validating our study methods. Further investigation found symptoms that characterized CD clinically and discovered a significant association between eosinophilic disorders of the esophagus and CD. Of 14 previously identified comorbidities, 8 were significantly associated with CD. Conclusions: An EHR-based PheWAS method is a powerful, efficient, and cost-effective method to screen for possible CD comorbidities and validate associations at the population level. Ours is the first PheWAS of CD to confirm a significant association of eosinophilic disorders of the esophagus with CD in a controlled study. Abstract : Supplemental Digital Content is available in the text